A Web-Based Student Grade Management Information System for SMP IP YAKIN West Jakarta - Ermelinda Angela Amfotis; Embun Fajar Wati (Jurnal Sistem Informasi dan Teknologi Informasi, 2025)
The world of technology is currently developing very rapidly in line with the great need for information. Currenly the computers has taken a very important role in any work related to data processing, assessment is very important in a learning, assessment is carried out by the teachers to determine the ability of students to master the learning objevtives that have been set. At the SMP IP YAKIN West Jakarta where every work on storing grades is stiil done manually. Judging from this working system, the author sees a lot of inefficiencies and effectiveness or inaccuracy. From this research, the author wants to design an information system application processing student grades at SMP IP YAKIN West Jakarta which aims to produce software. The waterfall research method is used in this study. In data collection, there are two types that need to be collected, namely primary data and secondary data, primary data is the result of observations and interviews from relevant sources, while secondary research data uses the technique of collecting learning data or reading experts. This research resulted in a student grade  processing application system, which is designed to help check grades quickly and precisely. Help in the search for student grades because of the grades stored in the database.